THE EFFECT OF WADIAH GIRO DEPOSITS, WADIAH SAVINGS DEPOSITS, AND WADIAH BONUSES ON RETURN ON EQUITY WITH FIRM SIZE AS A MODERATING VARIABLE IN ISLAMIC BANKING IN INDONESIA PERIOD 2018.Q1-2023.Q3 - Salsabila, Nisrina; Budianto, Eka Wahyu Hestya (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research studies the relationship between Wadiah Current Account, Wadiah Savings, Wadiah Bonus, and Return on Equity (ROE) in Islamic banks in Indonesia from 2018.Q1 to 2023.Q3. This study also explores how Firm Size moderates this relationship. Using purposive sampling method, 90 Islamic banks were selected over five years and four quarters. Panel Data Regression Analysis and Moderated Regression Analysis (MRA) were conducted using Eviews 12 software. The results of this study will explain the effect of wadiah demand deposits, savings investment funds, and deposit investment funds, and wadiah bonuses on ROE in Islamic banking in Indonesia for the period 2018.Q1-2023.Q3. This study will also explain the effect of frism size as a moderating variable on the relationship between variables with ROE.